2003
DOI: 10.1021/ic035111o
|View full text |Cite
|
Sign up to set email alerts
|

Three Topological Isomeric Coordination Polymer Networks from the Assembly of a Rigid Linear Spacer and a Square Planar Metal Node:  Structures, Isomerism Control, and Solid-to-Solid Transformation

Abstract: Assemblies of 1-methyl-1',2-bis(4-pyridyl)ethene (mpe) and Co(NCS)(2) afford three isomeric framework networks and different topological features depending on the assembly conditions. Isomerism control and solid-to-solid transformation phenomena are observed among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…11). 91 Solvent-mediated isomerization is actually a recrystallization phenomenon controlled by thermodynamic factors. The saturated solution of an unstable isomer is supersaturated for a more stable isomer.…”
Section: Crystal Isomerization Of Coordination Polymersmentioning
confidence: 99%
“…11). 91 Solvent-mediated isomerization is actually a recrystallization phenomenon controlled by thermodynamic factors. The saturated solution of an unstable isomer is supersaturated for a more stable isomer.…”
Section: Crystal Isomerization Of Coordination Polymersmentioning
confidence: 99%
“…Unfortunately, the energy difference between possible polymorphs or isomers is frequently small, which can lead to the formation of different products under kinetic or thermodynamic control . In this context, a large number of polymorphic and isomeric coordination compounds were reported in the last years , . From a viewpoint of material synthesis this might be of disadvantage but there is also some benefit from these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of new coordination compounds and polymers, inorganic–organic hybride compounds, and metal–organic frameworks is still a fast-growing field in chemistry, as they show potential for present or future applications. For any application some information on the stability of a given compound is required, which is especially the case for stable and metastable forms like, for example, polymorphs or isomers. In this case, on the one hand, the chemical composition is constant, and all differences in the physical properties, including thermodynamic parameters, depend entirely on the differences in the crystal structures and can be compared directly. On the other hand, even if several polymorphic or isomeric coordination compounds are reported, in most cases their thermodynamic relations are usually not investigated. Sometimes conclusions on the stability were drawn based on the comparison of the densities, the fact that one form transforms into another or by computational methods. In other cases, crystals of two modifications were obtained, and one of these forms can be prepared pure, whereas no access to the other form was found, and thus, it is concluded that the latter, frequently called “disappearing polymorph”, is metastable, which is not necessarily the case. Finally, these results are sometimes discussed in context of the crystal structure, where, for example, some short intermolecular contacts are held to be responsible for the stability of a given form. , All these might be incomplete because for definite conclusions the exact thermodynamic relations must be known, which for coordination compounds is difficult to investigate.…”
Section: Introductionmentioning
confidence: 99%